1999
DOI: 10.1093/nar/27.24.4687
|View full text |Cite
|
Sign up to set email alerts
|

Taz1p and Teb1p, two telobox proteins in Schizosaccharomyces pombe, recognize different telomere-related DNA sequences

Abstract: Band shift assays were used to study proteins from the fission yeast that bind double-stranded telomeric repeat sequences. We also examine general DNA binding properties of the telobox domain, which characterizes telomere-binding proteins from a range of species. We demonstrate that Taz1p has a high affinity for the fission yeast telomeric repeat, consistent with genetic results implicating this protein in telomere maintenance. A second Schizosaccharomyces pombe telobox protein, Teb1p, is shown to bind with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 0 publications
1
37
1
1
Order By: Relevance
“…Perhaps one of the most striking and intriguing findings in this study is that Taz1, a well-characterized DNAbinding protein highly specific to telomeric repeats (Cooper et al 1997;Vassetzky et al 1999;Spink et al 2000), accumulated at the fusion points of Type A circular chromosomes where there are no telomeric repeat. In budding yeast, it has been shown by ChIP analysis that the telomeric DNA-binding protein, Rap1, and its binding partners associate with subtelomeric regions in addition to telomeric repeats (Strahl-Bolsinger et al 1997;Lieb et al 2001;Smith et al 2003).…”
Section: Genetic Inheritance Of Taz1 At Subtelomeres In the Absence Omentioning
confidence: 67%
“…Perhaps one of the most striking and intriguing findings in this study is that Taz1, a well-characterized DNAbinding protein highly specific to telomeric repeats (Cooper et al 1997;Vassetzky et al 1999;Spink et al 2000), accumulated at the fusion points of Type A circular chromosomes where there are no telomeric repeat. In budding yeast, it has been shown by ChIP analysis that the telomeric DNA-binding protein, Rap1, and its binding partners associate with subtelomeric regions in addition to telomeric repeats (Strahl-Bolsinger et al 1997;Lieb et al 2001;Smith et al 2003).…”
Section: Genetic Inheritance Of Taz1 At Subtelomeres In the Absence Omentioning
confidence: 67%
“…Because yeast Rap1p functions both as a structural component of yeast telomeres and a transcriptional regulator (11,12), the presence of Myb-like domain and the involvement of transcriptional regulation may represent universal characteristics of telomere-binding proteins. This idea is further supported by the fact that a S. pombe telomeric protein, Teb1p, may function as a general transcription factor (24). An analysis of Arabidopsis DNA sequences available in data bases revealed that the sequence AAACCCTAA, corresponding to 1.3 units of the plant telomeric repeat AAACCCT, is preferentially located in the 5Ј region of the genes (29).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it has been shown that the isolated Myb-like domain of TRF1 binds specifically and with significant affinity to telomeric DNA as a monomer (20). Although with less specificity than the full-length dimer, the isolated Myb-like domain of Taz1p was also capable of sequence-specific DNA binding (23,24). Taken together, these results indicate that the Myblike domain is indeed responsible for specific telomeric DNA recognition.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Both factors bind in vitro to the duplex DNA repeats with high affinity 2 and binding does not require a DNA end. 3,4 However, very low affinity binding to single-stranded DNA has recently been demonstrated, 5 with a net preference for the G-strand. TRF1 and TRF2 are found to co-localise, in vivo, with telomeres of human metaphase chromosomes.…”
Section: Introductionmentioning
confidence: 99%